Assessment of genetic diversity among low-nitrogen-tolerant early generation maize inbred lines using SNP markers - Ajala, S.O.; Olayiwola, M.O.; Ilesanmi, O.J.; Gedil, Melaku A; Job, A.O.; Olaniyan, A.B. (Informa UK Limited, 2019)
Low soil nitrogen (low-N) level is responsible for yield reduction in maize (Zea mays L.) fields in sub-Saharan Africa. A clear understanding of the genetic diversity among early generation inbred lines selected from various elite low-N- tolerant populations offers an opportunity to obtain lines that could be used in parental combinations to develop high-yielding low-N-tolerant maize hybrids. A total of 115 S3 lines derived from four low-N-tolerant populations were assessed for genetic diversity using 15 670 single nucleotide polymorphism (SNP) markers. The SNP markers were highly polymorphic with polymorphic information content ranging from 0.0 to 0.38. The genetic diversity among the inbred lines ranged from 0.0 to 0.50 and thus indicated the high level of dissimilarity among the inbred lines. The neighbour-joining clustering algorithm and model-based population structure classified the 115 lines into four distinct groups that were generally consistent with the genetic backgrounds of the inbred lines. The information obtained from this study revealed genetic diversity among the inbred lines and may guide the selection of potential parents for detailed combining ability studies and eventual use in hybrid combinations. The selected inbred lines would be invaluable in the development of low-N-tolerant hybrids.